PRODUKTIVITAS DAN BIAYA PENYARADAN KAYU DENGAN KERBAU DI JAMBI - Dulsalam Dulsalam; Sukadaryati Sukadaryati (Jurnal Penelitian Hasil Hutan, 2001)
An investigation on productivity and logskidding cost using buffalo (Bubalus bubalis) was carried out at the area of lnhutani V in Jambi in 1999. The objective is to get reliable information about such productivity and cost. Connected with this purpose, some related data as collected were i.e. volume of skidded log, skidding distance, skiddingworking time, buffalo working time, feeding cost, operator cost, and equipment.Volumes of log which was skidded using buffalo ranged between 0.094 and 0.904 m3/tripwith an avverage of 0.484 m3/trip. Skidding distance using buffalo varied from 10 to 212 m with an average of 82 m. The working time varied from 11 to 83 minutes with an average of 30 minutes. The log skidding productivity ranged between 0.035 and 1.211 m3hm/hour with an average of 0.338 m3hmlhour. Log skidding costs using buffalo ranged between Rp 681 and Rp23.589 m3hm with an average of Rp 4.375/m3hm. It is suggested that volume of skidded log in each round trip and skidding distance be not more than 1 m3 and 250 m, respectively.